2019
DOI: 10.1038/s41598-019-41046-y
|View full text |Cite
|
Sign up to set email alerts
|

Association of symptoms of attention deficit-hyperactivity disorder and impulsive-aggression with severity of suicidal behavior in adult attempters

Abstract: Literature emphasizes the relationship between attention deficit-hyperactivity disorder (ADHD) and suicidal behavior (SB). However, the link between ADHD and the severity of SB is yet to be determined. We investigated the association between a probable diagnosis of ADHD and the severity of SB in 539 hospitalized suicide attempters, and determined the role of comorbid psychiatric diagnoses. The severity of SB was defined as the number of suicide attempts, age at first suicide attempt, seriousness and violence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 60 publications
2
15
0
Order By: Relevance
“…After mental health symptoms such as depression/anxiety and conduct were taken into account, ADHD symptoms remained associated with a trajectory of suicide attempts persisting into adulthood. Prior studies including systematic reviews in both adults and adolescents reported that mental health comorbidities largely explained the ADHD-suicide attempts link (Balazs & Kereszteny, 2017; Conejero et al 2019; Impey & Heun, 2012). Our results partly align with a population-based study of insurance claims showing stronger associations between ADHD diagnosis and repeated suicide attempts (hazard ratio 6.5), than for any attempts (hazard ratio 3.8), above and beyond comorbidities (Huang et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…After mental health symptoms such as depression/anxiety and conduct were taken into account, ADHD symptoms remained associated with a trajectory of suicide attempts persisting into adulthood. Prior studies including systematic reviews in both adults and adolescents reported that mental health comorbidities largely explained the ADHD-suicide attempts link (Balazs & Kereszteny, 2017; Conejero et al 2019; Impey & Heun, 2012). Our results partly align with a population-based study of insurance claims showing stronger associations between ADHD diagnosis and repeated suicide attempts (hazard ratio 6.5), than for any attempts (hazard ratio 3.8), above and beyond comorbidities (Huang et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…One study of 539 patients who had attempted suicide showed that SA were not associated with ADHD per se but with impulsive aggression, particularly when there were ADHD symptoms. 67 In patients with ADHD, treatment with CS such as methylphenidate reduces impulsivity and aggressive behavior. 68 , 69 Methylphenidate increases dopamine and norepinephrine activity through reuptake inhibition of both neurotransmitters.…”
Section: Discussionmentioning
confidence: 99%
“…This is especially relevant for women with ADHD, in light of the fact that one-quarter of Canadian adults with ADHD have attempted suicide. Additionally, given the genetic basis for impulsivity (Gray et al, 2018) and its influence on both ADHD and suicide (Conejero et al, 2019), it may be worth exploring whether assessment of suicidality of first-degree relatives of individuals with ADHD is warranted.…”
Section: Discussionmentioning
confidence: 99%